2011
DOI: 10.1007/s00125-011-2081-0
|View full text |Cite
|
Sign up to set email alerts
|

Ischaemia-induced retinal neovascularisation and diabetic retinopathy in mice with conditional knockout of hypoxia-inducible factor-1 in retinal Müller cells

Abstract: Aims/hypothesis Retinal Müller cells are known to produce inflammatory and angiogenic cytokines, which play important roles in diabetic retinopathy. Hypoxia-inducible factor (HIF)-1 has been shown to play a crucial role in retinal inflammation and neovascularisation. We sought to determine the role of Müller cell-derived HIF-1 in oxygeninduced retinopathy (OIR) and diabetic retinopathy using conditional Hif-1α (also known as Hif1a) knockout (KO) mice. Methods Conditional Hif-1α KO mice were generated by crossi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(77 citation statements)
references
References 43 publications
8
69
0
Order By: Relevance
“…Interestingly, TNF-α expression was found to be elevated in the retinas of diabetic wild-type mice but not in VEGF-A knockouts. Similar results were obtained by Lin and coworkers when they observed that Müller cell-specific disruption of the hypoxia-inducible factor 1 gene resulted in diminished expression of VEGF and ICAM-1, as well as reduced leukostasis and vascular permeability in mice made diabetic with STZ [44].…”
Section: Evidence For Inflammation In Drsupporting
confidence: 86%
“…Interestingly, TNF-α expression was found to be elevated in the retinas of diabetic wild-type mice but not in VEGF-A knockouts. Similar results were obtained by Lin and coworkers when they observed that Müller cell-specific disruption of the hypoxia-inducible factor 1 gene resulted in diminished expression of VEGF and ICAM-1, as well as reduced leukostasis and vascular permeability in mice made diabetic with STZ [44].…”
Section: Evidence For Inflammation In Drsupporting
confidence: 86%
“…Over the past decade, almost all retinal cells have been shown to express HIF-1α and VEGF in DR. In this context, recent studies using conditional KO mice models have suggested that the Müller cell-derived HIF-1α and VEGF has a causative role in the major pathologic changes in DR [27,28] . Increasing evidence suggests that hyperglycemia induces changes in the retinal [Ca 2+ ] i dynamics [2,4] , which have been associated with distinct pathological processes, such as DR.…”
Section: Discussionmentioning
confidence: 99%
“…Mice with streptozotocin (STZ)-induced diabetes show elevated VEGF levels in the retina; however, this increase was not seen in mice with a conditional knockout of hypoxiainducible factor-1α (HIF-1α) in the Müller glial cells. Moreover, when the same mice were tested in the oxygen-induced retinopathy model, in which retinal neovascularization occurs in response to excessive VEGF expression, the HIF-1α deficiency decreased the pathological neovascularization in the retina [26]. Other group also reported that Müller glial cell-derived VEGF is essential for diabetes-induced retinal inflammation and vascular leakage [27].…”
Section: Neuroinflammatory Signaling and Cellular Disorders In The Rementioning
confidence: 97%
“…Interleukin-6 (IL-6) mRNA is expressed in the retinal ganglion cells and inner nuclear layer cells, including the Müller glial cells [25]. Retinal ganglion cells express additional cytokines such as vascular endothelial growth factor (VEGF) [26], which contributes to the pathogenesis of diabetic retinopathy. Mice with streptozotocin (STZ)-induced diabetes show elevated VEGF levels in the retina; however, this increase was not seen in mice with a conditional knockout of hypoxiainducible factor-1α (HIF-1α) in the Müller glial cells.…”
Section: Neuroinflammatory Signaling and Cellular Disorders In The Rementioning
confidence: 99%